Stewardship of Prehospital Low Titer O-Positive Whole Blood in a Large Urban Fire-Based EMS System. (2nd November 2022) - Bullock, William; Schaefer, Randall; Wampler, David; Stringfellow, Michael; Dieterle, Mark; Winckler, Christopher "CJ"
Abstract: Introduction: Trauma is the leading cause of death for those aged 1 to 46 years with most fatalities resulting from hemorrhage prior to arrival to hospital. Hemorrhagic shock patients receiving transfusion with 15 minutes experience lower mortality. Prehospital blood transfusion has many legal, fiduciary, and logistical issues. The San Antonio Fire Department participates in a consortium designed to enhance the stewardship of prehospital whole blood. This study aimed to stratify blood usage amongst the field supervisors and special operations units that carry whole blood. Methods: This was a 12-month retrospective analysis of blood usage. Blood tracking forms (used for either blood exchange of transfusion) were cross referenced with city financial records to determine blood usage patterns in the 7th Largest City in the US. We used descriptive statistics, compared usage ratios, and chi-square to compare dichotomized data. Results: A total of 363 whole blood units were obtained and 248 (68.3%) units of whole blood were transfused. EMS field supervisors transfused 74% of whole blood vs. 44% for special operations ambulances (p= <0.001). Response vehicles located in densely populated areas had the highest usage rates. All blood units were either transfused or returned for a zero blood unit wastage for expiration. Conclusion: The information contained within this work can provide other EMS agencies with a basic framework for comparison. The data from the SAFD's whole blood transfusion rate coupled with the clinical transfusion guideline has provided some insight for prospective agencies considering adopting a whole blood program. EMS systems and municipalities with similar characteristics can project their own whole blood needs and make informed decisions regarding program feasibility and design.